A longitudinal investigation of the relationship between crowding and reading: A neurodegenerative approach. (May 2016) - Yong, Keir; Rajdev, Kishan; Warrington, Elizabeth; Nicholas, Jennifer; Warren, Jason; Crutch, Sebastian
Abstract: We have previously documented two patients (FOL and CLA) with posterior cortical atrophy who achieved accurate and rapid reading despite deficits in ten measures of visual processing, with two notable exceptions: (1) a measure of visual acuity, (2) a measure of visual crowding. Subsequent longitudinal investigation of these patients was carried out, involving annual tests of early visual, visuoperceptual and visuospatial processing and assessment of reading ability. Follow-up assessments identified the evolution of a particular early visual processing deficit, excessive visual crowding; this deficit has been previously implicated in forms of dyslexia. Consistent with the link between crowding and reading dysfunction, follow-up assessments also revealed deterioration in both patients' reading ability. The current findings demonstrate a neurodegenerative approach towards understanding the relationship between visual crowding and the reading system, and suggest possible mechanisms for how excessive crowding may disrupt word recognition. Highlights: Two patients demonstrate remarkably intact reading despite grave visual impairment. Longitudinal assessments of visual function and reading ability were carried out. Emergence of excessive crowding in central vision was observed in both patients. Emergence of crowding was accompanied by a decline in reading ability. Findings demonstrate a neurodegenerative approach towards acquired dyslexia.